ATTITUDES TOWARD EXTENSIVE READING AMONG ENGLISH TEACHERS OF SENIOR HIGH SCHOOLS - Ima Dwi Lailatul Firda; Utami Widiati; Ekaning Dewanti Laksmi; Nur Hayati (Universitas Negeri Malang, 2018)
Abstract: Attitudes Toward Extensive Reading Among English Teachers of Senior High Schools. This survey aims to investigate the attitudes of 32 English teachers of public senior high schools in a district in East Java Province, Indonesia, toward Extensive Reading (ER) as one of the ways of improving reading habit, covering the teachers’ cognitive, behavioral, and affective attitudes. Questionnaires in the form of closed-ended and open-ended questions were used as the main instrument to collect the data, complemented with interviews with sampled teachers to gain more in-depth understanding of the phenomena under study. The results show that cognitively, most English teachers have positive cognitive attitudes, which implies good understanding of ER. The teachers’ affective attitudes also reflect their eagerness to know more about implementing ER and to find ways of solving potential problems. However, in terms of behavioral attitudes, the data show that the teachers are still in doubt to conduct ER program due to several problems, such as time allotment, reading resources, students’ motivation, curriculum and school programs, learning assessment, and school rules. The findings imply the need for policy makers at school and government’s educational agencies, as well as experts in the field to help support the teachers in setting up ER program at schools by addressing the issues that teachers are concerned with.Abstrak: Sikap Guru Bahasa Inggris Sekolah Menengah Atas Terhadap Membaca Ekstensif. Studi survei ini bertujuan untuk menyelidiki sikap (kognitif, konatif, dan afektif) dari 32 guru bahasa Inggris Sekolah Menengah Atas di salah satu kota di Provinsi Jawa Timur, Indonesia, terhadap membaca ekstensif sebagai salah satu cara untuk meningkatkan kebiasaan membaca. Kuesioner dalam bentuk pertanyaan tertutup dan terbuka digunakan sebagai instrumen utama untuk mengumpulkan data, serta dilengkapi dengan wawancara dengan guru sampel untuk mendapatkan pemahaman mendalam tentang fenomena yang diteliti. Hasil penelitian menunjukkan bahwa secara kognitif, sebagian besar guru bahasa Inggris memiliki sikap kognitif positif, yang menyiratkan pemahaman yang baik tentang membaca ekstensif. Sikap afektif guru juga mencerminkan keinginan mereka untuk mengetahui lebih banyak tentang penerapan membaca ekstensif dan untuk menemukan cara memecahkan masalah potensial. Namun, dalam hal sikap konatif, data menunjukkan bahwa guru masih ragu untuk melakukan program membaca ekstensif karena beberapa masalah, seperti alokasi waktu, sumber bacaan, motivasi siswa, kurikulum dan program sekolah, penilaian pembelajaran, dan peraturan sekolah. Hasil-hasil ini menyiratkan perlunya pembuat kebijakan di sekolah dan lembaga pendidikan pemerintah, serta para ahli di lapangan untuk membantu mendukung para guru dalam menyiapkan program membaca ekstensif di sekolah-sekolah dengan menangani isu-isu yang berkaitan dengan guru.